Concurrent phosphorus doping and reduction of graphene oxide - Poh, Hwee Ling (2014)
Doped graphene materials are of huge importance because doping with electron-donating or electron-withdrawing groups can significantly change the electronic structure and impact the electronic and electrochemical properties of these materials. It is highly important to be able to produce these materials in large quantities for practical applications. The only method capable of large-scale production is the oxidative treatment of graphite to graphene oxide, followed by its consequent reduction. We describe a scalable method for a one-step doping of graphene with phosphorus, with a simultaneous reduction of graphene oxide. Such a method is able to introduce significant amount of dopant (3.65 at. %). Phosphorus-doped graphene is characterized in detail and shows important electronic and electrochemical properties. The electrical conductivity of phosphorus-doped graphene is much higher than that of undoped graphene, owing to a large concentration of free carriers. Such a graphene material is expected to find useful applications in electronic, energy storage, and sensing devices.